Avaliação da atividade mucolítica e antiinflamatória do BromAc® aplicado ao tratamento da COVID-19 - Geovane Marques Ferreira (2023)
COVID-19 is a deadly disease caused by the SARS-CoV-2 pandemic, which has remained a public health threat for over three years. In contrast to the severity of COVID-19, so far, there are few drugs capable of efficiently preventing or delaying the development of severe COVID-19. More importantly, studies focusing on compounds controlled intranasally to act more quickly in the airways and mucous membranes of individuals with severe COVID-19 under mechanical ventilation are still reduced. In this sense, BromAc® is a combination of bromelain and acetylcysteine (NAC), currently used for the treatment of pseudomyxoma (Phase 3) and has been studied for repositioning in the treatment of COVID-19. Therefore, in the present study, we sought to examine the mucolytic and anti-inflammatory effect of BromAc® ex-vivo in a sample of tracheal aspirates from critically ill patients with COVID-19 under mechanical ventilation and the anti-inflammatory effect of BromAc® in an in vitro system using peripheral blood cells stimulated with inactivated SARS-CoV-2. Our results sadden that BromAc® exhibited a robust mucolytic effect in the exception of tracheal aspirates from patients with COVID-19 in a dose-dependent manner. In addition, BromAc® has demonstrated anti-inflammatory activity, reducing the cytokine storm in the tracheal aspirate samples from patients with COVID-19 and in culture supernatants. The combination showed reduced chemokines compared to NAC individually. The action of the combined compounds on regulatory cytokines such as IL-10 was also observed. Furthermore, BromAc® was able to modulate CD16+ and CD14+ cells after in vitro treatment of blood cells with BromAc®. These results indicate a robust mucolytic and anti-inflammatory effect of BromAc® in tracheal aspirates from critically ill patients, indicating its potential as a therapeutic strategy for COVID-19. Clinical trials are needed to define the safety and efficacy of BromAc® in the treatment of the disease, which has been the greatest challenge of the 21st century.